Experience of training and certification in pediatric disciplines of students majoring in 222 "medicine" specialty - O.P. Volosovets; O.M. Naumenko; R.S. Tsymbaliuk; S.P. Kryvopustov; N.V. Grischenko; O.V. Mozyrska; I.O. Loginova; T.I. Shevtsova; O.F. Chernii; S.D. Saltanova; O.L. Kovalchuk; M.V. Kryvopustova (Zaslavsky O.Yu., 2023)
Certification of graduates of the Faculty of Medicine 2 of the National Medical University (NMU) in pediatric disciplines was conducted by the Department of Pediatrics 2 at the objective structured practical (clinical) exam 2 (OSP(C)E-2) station "Initial and resuscitation care to a newborn child" on the basis of the Educational and Scientific Center of Medical Simulations of the NMU. The methodology that we introduced in 2022 in the Medical Education journal was presented and approved at the methodical meeting of the heads of departments of pediatrics of higher education institutions of Ukraine during the Sidelnikov readings. The data of an anonymous survey of graduates demonstrated that most respondents (93.4 % of domestic and 91.9 % of foreign ones) were satisfied with the volume of the station and its practical orientation. The students noted that during preparation to exam, this particular model of the station allows them to master, when using mannequins, manipulations according to the algorithm of initial and resuscitation care to a newborn child, which can be useful under various circumstances in wartime conditions. Out of 338 students of the Faculty of Medicine 2, 303 (89.6 %) passed the OSP(C)E-2 exam with an "excellent" grade, 32 (9.4 %) with a "good" grade, and 3 (0.9 %) with a "satisfactory" grade. The issue of optimality and adequacy of assessing only the skills in initial and resuscitation care to a newborn child at the OSP(C)E-2 exam remained debatable among teachers. This corresponds to the opinion of 8.1 % of domestic and 6.6 % of foreign students who believe that for perfection and objectivity of pediatric skills assessment, it would be desirable to introduce one more pediatric station for the OSP(C)E-2 exam with the involvement of a virtual a patient of a different age. Experience of certification in pediatric disciplines of higher education graduates majoring in 222 "medicine" specialty at the Bogomolets National Medical University, both teachers and students, testified to its effectiveness and objectivity in assessing the special competencies of graduates in providing resuscitation care to a newborn child.